Transforming agriculture in Odisha: Sources and drivers of agriculture growth - Anwarul Hoda; Pallavi Rajkhowa; Ashok Gulati (Indian Council for Research on International Economic Relations (ICRIER), 2017)
Odisha is one of the poorest states in the country, with around 36 per cent of the rural population living below the poverty line. Ninety one per cent of poverty in Odisha is rural and more than 60 per cent of its workforce is engaged in agriculture. During the five years from 2010-11 to 2014-15, the contribution of agriculture to the state GDP recorded an annual average growth of a mere 0.9 per cent. This paper studies the composition, sources and potential drivers of agriculture growth in Odisha with a view to identifying the factors for the state's poor performance in the sector. In light of the findings, it makes three principal recommendations to stimulate agricultural growth in the state. viz., expansion of irrigation facilities, increase in the intensity of surfaced roads in rural areas and diversification of production portfolio towards high value commodities. The main scope for expanding irrigation lies in the largely untapped ground water resources; this requires that quality and quantity of rural power supply be improved by strengthening transmission and distribution and separating the feeders for irrigation. The proportion of surfaced roads in the state is one of the lowest in the country and needs attention to link farmers to markets. The state is already making progress towards the development of the livestock sector and the production of fruits and vegetables but the process needs to be accelerated through extension services.
Keywords: Q10; Q15; Q25; 330; Agricultural Growth; Irrigation; Power; Surfaced Roads; Agriculture Diversification; Odisha